2010
DOI: 10.1016/j.bmcl.2010.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Role of the phenolic hydroxyl group in the biological activities of simplified analogue of aplysiatoxin with antiproliferative activity

Abstract: The 18-deoxy derivative (3) of a simplified analogue (1) of aplysiatoxin with antiproliferative activity was synthesized to examine the role of the phenolic hydroxyl group at position 18 in the biological activities of 1. Compound 3 as well as 1 showed significant affinity for protein kinase Cδ (PKCδ), and the antiproliferative activity of 3 was slightly higher than that of 1. However, the anti-tumor-promoting activity of 3 was less than that of 1 in vitro, suggesting that the phenolic hydroxyl group of 1 is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
2
13
1
Order By: Relevance
“…10) Only weak EA-induction (9.0% and 7.1% at 10 À6 and 10 À7 M respectively) and significant suppression of TPA-induced EA production (5.0% and 7.2% at 10 À6 and 10 À7 M respectively) were observed, suggesting that 3 is a better anti-tumor promoter than Aplog-1. Although our previous study using 2 found no correlation between inhibition of TPA-induced EA production and suppression of proliferation of tumor cells, 14) introduction of the geminal dimethyl group into position 12 of Aplog-1 was found to enhance both activities.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…10) Only weak EA-induction (9.0% and 7.1% at 10 À6 and 10 À7 M respectively) and significant suppression of TPA-induced EA production (5.0% and 7.2% at 10 À6 and 10 À7 M respectively) were observed, suggesting that 3 is a better anti-tumor promoter than Aplog-1. Although our previous study using 2 found no correlation between inhibition of TPA-induced EA production and suppression of proliferation of tumor cells, 14) introduction of the geminal dimethyl group into position 12 of Aplog-1 was found to enhance both activities.…”
Section: Resultscontrasting
confidence: 62%
“…21,22,24) We found previously that Aplog-1 displayed binding and activation profiles for PKC similar to those of Bryo-1, and that its antiproliferative activity was closely correlated with its affinity for PKC. 10,14) The affinity of 3 for PKC was measured in a competition binding assay with [ 3 H]phorbol 12,13-dibutyrate (PDBu). 25) Compound 3 exhibited strong affinity for PKC (K i ¼ 5:9 nM), about 2.5 times higher than that of Aplog-1 (K i ¼ 15 nM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplysiatoxin (ATX) and debromoaplysiatoxin (DATX) are 12- O -tetradecanoylphorbol-13-acetate (TPA)-type tumor promoters which activate PKC as with lyngbyatoxin A ( 2 ) [6,29]. It was reported that K i values of ATX and DATX for binding to PKCδ-C1B are 0.41 nM [35,36] and 0.20 nM [37], respectively. These K i values are comparable to that of compound 2 obtained in this study.…”
Section: Resultsmentioning
confidence: 99%
“…27.7), with potent antiproliferative properties as potential anticancer agents [95][96][97][98][99][100][101][102][103]. These synthetic analogues have been shown to inhibit the action of tumor promotors as well as prevent growth of cancer cells in similar ways to bryostatin 1.…”
Section: Aplysiatoxinsmentioning
confidence: 94%